Analysis on the Translation of Technical Terms in Disaster Management: A Case Study in News Translation by Novice Translators - Nur Saptaningsih (Faculty of Language and Literature, University of Surakarta, 2018)
Technical term is a word that has a specific meaning within a specific field of expertise. Translation of technical terms is challenging and becomes one of the most factors influencing the process of translation. This paper discusses about the pattern of translation of technical terms in disaster management, with the focus on translation techniques and translation quality. This study analyses the translation of technical terms made by novice/student translators. The data include words and phrases belonging to technical terms in disaster management. The translation techniques used by the translators to render the meaning of the technical terms in disaster management were categorized based on those proposed by Molina and Albir (2002). The translation quality was measured with the translation quality assessment proposed by Nababan, Nuraeni, and Sumardiono(2012). Patterns of translation were then drawn. The examination reveals that there are three patterns used by eight translators in conveying the meaning of technical terms in disaster management. This study also pinpoints possible causes underlying the usage of translation technique in search of equivalences